Association of years of occupational quartz exposure with spirometric airflow limitation in Norwegian men aged 30–46 years. Issue 8 (1st August 1998) - Humerfelt, Sjur; Eide, Geir E; Gulsvik, Amund
Abstract : BACKGROUND: The association between occupational quartz exposure and ventilatory function was investigated in men in a general population after adjusting for other potential determinants of outcome. METHODS: All eligible men aged 30–46 years living in western Norway (n = 45 380) were invited to a cross sectional community survey. This included a self administered questionnaire (with respiratory symptoms, smoking habits and occupational exposures), spirometric recordings (using dry wedge bellow spirometers), and a chest radiograph (65% attendance). Measurements of forced expiratory volume in one second (FEV1 ) and forced vital capacity (FVC) were obtained in 91% (n = 26 803) of those who participated, 26 106 of whom performed successful spirometric tests and had normal chest radiographs and remained for further analysis. Age, body mass index, and technician standardised residuals ((observed minus predicted value)/residual standard error) of maximum FEV1 /height 2 and FVC/height 2 were used as outcome variables for adjusted lung function levels, respectively. RESULTS: Occupational quartz exposure was reported by 13% (n = 3445) of those who participated in the survey, with a mean duration of seven years. Among those exposed to quartz, significant inverse linear relationships were observed between years of exposure and FEV1 level and the ratio of FEV1 /FVC, independent of host characteristics. Multiple linear regression analyses showed that the difference in FEV1 associated with each year of quartz exposure was –4.3 ml (95% Cl –1.1 to –7.5 ml; p = 0.01) compared with –6.9 ml (95% Cl –4.7 to –9.1 ml; p<0.01) from smoking 20 cigarettes/day for one year after adjusting for age, atopy, asthma, wheezing, marital status, and other occupational exposures. CONCLUSION: In men aged 30–46 years with occupational quartz exposure and normal chest radiographs the duration of occupational quartz exposure was an independent predictor for spirometric airflow limitation.